Inovasi Pelayanan Skck Online Terhadap Kepuasan Masyarakat Di Polres Gresik - Supriyanto Supriyanto; Windy Indrawati (FISIP UWP, 2022)
The purpose of this study was to determine the effect of the online SKCK service innovation on community satisfaction at the Gresik Police. The background of this research is the best practices shown by the Gresik Police in implementing the SKCK Online innovation. Best practice is manifested in the award given by KemenPAN-RB in the very good category received by the Gresik Police. In this study, the theory used is the theory of innovation by Muluk with innovation criteria based on the General Guidelines for State Administration Innovation (2015) and the theory of satisfaction by Lovelock and Wirtz by measuring public satisfaction based on the Regulation of the Minister of State Civil Service Empowerment Number 14 of 2017 concerning Guidelines for Preparing Satisfaction Surveys Public. This research uses quantitative research methods. Research location at Polres Gresik. The data collection technique was carried out by distributing questionnaires. The partial test (t test) and t test results indicate that there is a significant difference between t count and t table. The value of t count is 50.417 at the level of significance (Sig.) Of 0.000. This means that the t value is greater at the probability level of 0.05 (95%) to obtain a t table of 1.682. So it can be concluded from this study that there is an influence of online SKCK service innovation on public satisfaction at the Gresik Police.